SKRINING RISIKO GANGGUAN SPEKTRUM AUTISME PADA ANAK USIA 16–30 BULAN MENGGUNAKAN INSTRUMEN M-CHAT DI PEKON TAMBAHREJO KABUPATEN PRINGSEWU - Mutiara, Erina Citra; Santriani, Lara Santriani; Kusuma, Intan Widia; Oktavia, Nadia (PITIMAS: Journal of Community Engagement in Health, 2025)
Autism Spectrum Disorder (ASD) is a developmental condition that affects a child's ability to interact socially, communicate, and exhibit certain behaviors. Early detection is crucial in determining the effectiveness of interventions and improving the child's quality of life. This community service program is designed to broaden the understanding of parents and health center staff regarding the urgency of early autism risk screening through the Modified Checklist for Autism in Toddlers (M-CHAT). The program was implemented in Pekon Tambahrejo, Pringsewu District, involving 20 children aged 16 to 30 months and their parents. The implementation approach includes information sessions, M-CHAT form filling simulation exercises, active participant discussions, and pre- and post-tests to measure knowledge improvement. The program results showed an increase in participants' knowledge from 60% to 90% after education, reflecting the success of interactive learning methods. Based on the M-CHAT screening, all children examined showed “normal” results or were not at risk of autism. These findings indicate that education and training initiatives can raise public awareness of the importance of early detection of developmental disorders. In addition, this program serves as an example of the application of M-CHAT screening in maternal and child health (MCH) services at community health centers and integrated health service posts, thereby supporting promotion and prevention activities in the First 8000 Days of Life Program.